IMPLEMENTATION OF THE PROJECT BASED LEARNING METHOD FOR DEVELOPING STUDENT COMPETENCIES THROUGH MAKING TRADITIONAL ACEHNESE UMBRELLAS - Sarah Nadia (Journal Informatic, Education and Management (JIEM), 2026)
One of the learning methods that supports the OBE curriculum is the Project Based Learning method. This method requires students to work together to complete projects or assignments that are relevant to the learning material, namely making traditional Acehnese umbrellas. The method used is included in Research and Development , aimed at producing products and testing the effectiveness of certain products. The development model used refers to the 4D development model. The research sample used to determine the responses of 100 students regarding traditional Acehnese umbrella products. Furthermore, the results of research and development on making traditional Acehnese umbrellas can be described as follows: (1) Fashion Experts, the overall assessment aspect obtained a percentage of 91.67%, which is in the very good or very decent category. The results of the fashion expert assessment show that the developed traditional Acehnese umbrella product can train students’ creative and motor skills in applying motifs, sewing kasab threads, and processing decorative knick-knacks. (2) Cultural experts, the overall assessment aspect obtained a percentage of 93.75%, which is in the very good or very decent category. (3) Respondents’ assessment of the development of traditional Acehnese umbrellas is (53.16:6,000) x 100% = 88.6 of the expected (100%). Thus, the traditional umbrellas developed have received a positive response in terms of shape, color, motif, aesthetics, persuasiveness, and affordable price. Therefore, through the implementation of the Project Based Learning Method, it can increase students’ creativity or innovation as an outcome in the Acehnese Traditional Crafts Course.